Coupling of submersible microbial fuel cell into aerobic granular sludge bioreactor for ciprofloxacin stress alleviation: Performance and mechanism. (1st November 2022) - Zhao, Chuanfu; Meng, Shuangyu; Yan, Liangguo; Zhang, Xinwen; Wei, Qin; Wei, Dong
Abstract: Ciprofloxacin (CIP) is widely existed in wastewater treatment systems, which can cause significant toxicity effect and sludge damage under long-term stress due to its remarkable chemical stability. Herein, a novel submersible microbial fuel cell (MFC) coupling of aerobic granular sludge (AGS) bioreactor was designed to simultaneously mitigate the CIP toxicity and improve system treating performance. At stable phase, the average NH4 + -N, COD and CIP removal efficiencies in AGS-MFC were improved to 99.1%, 92.1% and 83.2%, whereas the AGS-Control were only 97.4%, 65.9% and 46.1%, respectively. The long-term exposure of CIP affected the morphology of AGS in the control group, resulting in a lower particle size than that in the AGS-MFC group. Moreover, less EPS was secreted in the AGS-MFC group than that of AGS-Control group due to the MFC alleviated the CIP toxicity. From functional microorganisms and metabolism pathways, Corynebacterium and Rhodococcus with drug-resistant electricity generation were enriched in the anodic biofilm. The predesign of submersible MFC significantly reduced the transmission of resistance genes (qnrS) in AGS. Additionally, Cytochrome P450-mediated microbial metabolism may be a potential way to achieve CIP removal in submersible MFC-AGS. The results of this study could provide an effective strategy for treating toxic wastewater by using MFC and AGS, and are of great significance for further understanding the collaborative mechanism of contaminant removal. Graphical abstract: Image 1 Highlights: Submersible MFC coupled into AGS bioreactor mitigated the toxicity of CIP. AGS-MFC maintained better pollutant removal and electrochemical performance. MFC alleviated EPS overrelease, particle breakage and ARGs leakage caused by CIP. The qnrS and EABs formed a strong cooperative correlation expression network. Cytochrome P450 was a possible CIP degradation metabolic pathway of defluorination.